2001
DOI: 10.1172/jci9862
|View full text |Cite
|
Sign up to set email alerts
|

In vivo acceleration of heart relaxation performance by parvalbumin gene delivery

Abstract: Defective cardiac muscle relaxation plays a causal role in heart failure. Shown here is the new in vivo application of parvalbumin, a calcium-binding protein that facilitates ultrafast relaxation of specialized skeletal muscles. Parvalbumin is not naturally expressed in the heart. We show that parvalbumin gene transfer to the heart in vivo produces levels of parvalbumin characteristic of fast skeletal muscles, causes a physiologically relevant acceleration of heart relaxation performance in normal hearts, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 26 publications
6
76
1
Order By: Relevance
“…Further confirmation of the ability of parvalbumin to restore diastolic parameters to normal was obtained in an in vivo setting, in which injection of parvalbumin into the LV free wall both accelerated myocardial relaxation under physiological conditions and improved myocardial twitch relaxation rates and ϪdP/dt in hypothyroid hearts to normal. 10 In this study, we demonstrate that adenoviral gene transfer of parvalbumin, a protein affecting solely the lusitropic properties of myocardium, can be used to successfully transduce senescent myocytes and significantly improves myocardial relaxation in healthy senescent cardiac myocytes. The calcium transient decay rate is significantly improved in senescent parvalbumin-transduced myocytes compared with GFP-expressing and control myocytes, and the time from peak to 50% calcium in senescent myocytes transduced with parvalbumin is comparable to that of adult controls.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Further confirmation of the ability of parvalbumin to restore diastolic parameters to normal was obtained in an in vivo setting, in which injection of parvalbumin into the LV free wall both accelerated myocardial relaxation under physiological conditions and improved myocardial twitch relaxation rates and ϪdP/dt in hypothyroid hearts to normal. 10 In this study, we demonstrate that adenoviral gene transfer of parvalbumin, a protein affecting solely the lusitropic properties of myocardium, can be used to successfully transduce senescent myocytes and significantly improves myocardial relaxation in healthy senescent cardiac myocytes. The calcium transient decay rate is significantly improved in senescent parvalbumin-transduced myocytes compared with GFP-expressing and control myocytes, and the time from peak to 50% calcium in senescent myocytes transduced with parvalbumin is comparable to that of adult controls.…”
Section: Discussionmentioning
confidence: 77%
“…9 Adenoviral transduction of parvalbumin into the LV free wall has been shown to significantly accelerate LV isovolumic relaxation times in normal animals and also to restore normal relaxation performance in hypothyroidisminduced diastolic dysfunction. 10 In addition, adenoviral gene transfer of parvalbumin into adult myocytes in vitro has been shown to significantly increase the rate of myocyte relaxation (ϪdL/dT max , t 1/2R ) and to decrease the rate of decay of the intracellular calcium transient. Not only were relaxation parameters in normal adult myocytes improved, but also, in hypothyroid animals, parvalbumin gene delivery fully corrected diastolic dysfunction by improving myocyte relaxation to levels seen in control animals.…”
mentioning
confidence: 99%
“…Conversely, the overexpression of PV by injection of Pvalb cDNA into the rat slow-twitch muscle, soleus, significantly increases the speed of relaxation, without affecting the contraction (Muntener et al 1995). Pvalb gene delivery in rat heart in vivo increases the rate of heart relaxation in normal hearts and in an animal model of slowed cardiac muscle relaxation (Szatkowski et al 2001). Thus, PV or genetically "tuned" PV variants are discussed as potential tools to enhance cardiac diastolic function (Rodenbaugh et al 2007;Wang and Metzger 2008).…”
Section: Functional Aspects Of Parvalbumin and Oncomodulinmentioning
confidence: 99%
“…For instance, the gene for parvalbumin was expressed in the hearts of Sprague-Dawley rats. 17 The protein's presence was verified by immunofluorescence. The investigators demonstrated a substantial increase in diastolic relaxation.…”
Section: Right-and Left-sided Pressures At Cardiac Catheterization (Mmentioning
confidence: 99%